CPA - مقارنة بين التمويل التقليدي والتمويل الاسلامي للمشاريع العقارية في الجزائر دراسة حالة بنك القرض الشعبي الجزائري وكالة سوق اهراس - هناء نواري; فاطمة خليفة (My University, 2022)
This study aims to compare between traditional financing and Islamic financing for real estate projects in Algeria, which are financed within the framework of the CPA Bank of Algeria at Souk Ahras Agency, whether in terms of concepts, procedures for granting financing or the cost of financing. It also aims to help the applicant for this type of project to choose and determine the optimal financing for their projects and the least costly. In this study, it was concluded that traditional financing is based in calculating its returns on usurious interests, while Islamic financing is based on calculating its profits on the profit-sharing ratio or on the known profit margin rate. It was also reached that the procedures for granting financing for both financing are similar, and the difference lies only In the period granted by the bank to pay the first due payment, it was also concluded that the financing cost for both financings is very close, and this is in the event that the required interest rate in the case of conventional financing is equal with the rate of the profit margin known in the case of Islamic financing, according to the Murabaha - real estate formula. .................................................. تهدف هذه الدراسة إلى المقارنة بين التمويل التقليدي و التمويل الإسلامي للمشاريع العقارية في الجزائر , والممولة في إطار بنك القرض الشعبي الجزائري CPA بوكالة سوق أىراس سواء من حيث المفاىيم أو إجراءات منح التمويل أو تكلفة التمويل. كما تهدف إلى مساعدة طالب التمويل لهذا النوع من المشاريع على اختيار وتحديد التمويل الأمثل لمشاريعهم و الأقل تكلفة . وتم التوصل في ىذه الدراسة إلى أن التمويل التقليدي يرتكز في حساب عوائده على الفوائد الربوية , بينما التمويل الإسلامي يرتكز في حساب أرباحو على نسبة المشاركة في الإرباح أو على معدل ىامش الربح المعلوم .كما تم التوصل إلى تشابو إجراءات منح التمويل لكلا التمويلين ,ويكمن الاختلاف فقط في المدة التي يمنحها البنك لتسديد أول دفعة مستحقة , كما تم التوصل إلى أن تكلفة التمويل لكلا التمويلين متقاربة جدا , وىذا في حالة تساوي معدل الفائدة المطلوب في حالة التمويل التقليدي مع معدل ىامش الربح المعلوم في حالة التمويل الإسلامي وذلك حسب صيغة مرابحة –عقار.